Reversal from endothermic to exothermic behavior of imidazolium-based ionic liquids in molecular solvents - Rai, Gitanjali; Kumar, Anil (Chemical Physics Letters, 2010)
In this communication, we present an interesting reversal in the enthalpic behavior from endothermic to exothermic on increasing the carbon chain length attached to the imidazolium ring in the imidazolium-based ionic liquids. A systematic investigation is presented on the excess partial molar enthalpy, H(IL)(E) directly measured using isothermal titration calorimeter at 298.15 K for the interactions operating between cation and anion of four imidazolium ionic liquids with aqueous and various non-aqueous solvents. This reversal behavior is analyzed in terms of hydrophobic and solvation effects. (C) 2010 Published by Elsevier B.V.